Electronic Health Records Aggregators (EHRagg) - Prados-Suárez, Belén; Molina Fernández, Carlos; Yañez, Carmen Peña (Methods of Information in Medicine, 2020)
Background Integration of health data systems is an open problem. Most of the active initiatives are based on the use of standards. However, achieving a widely and generalized compliment of such standards still seems a costly task that will take a long time to be completed. Even more, most of the standards are proposed for a specific use, without integrating other needs.Objectives We propose an alternative to get a unified view of health-related data, valid for several uses, that unites heterogeneous data sources.Methods Our proposal integrates developments made so far to automatically learn how to extract and convert data from different health-related systems. It enables the creation of a single multipurpose point of access.Results We present the EhRagg notion and its related concepts. EHRagg is defined as a middleware that, following the FAIR principles, integrates health data sources offering a unified view over them.
Keywords: health data; interoperability; FAIR principles; text mining